1988
DOI: 10.4138/1653
|View full text |Cite
|
Sign up to set email alerts
|

40Ar/39Ar hornblende ages from southwestern Maine: evidence for Late Paleozoic metamorphism

Abstract: 40Ar/39Ar analyses of hornblendes from a 120 km long NE-trending transect within the high-grade rocks of the Casco Bay Group provide information regarding the timing of thermal events and subsequent cooling history of this region. In the north, plateau ages of 368-372 Ma record the time of cooling through argon closure temperatures (500°C) following Acadian metamorphism. In the central portion of the transect, hornblendes display younger ages (350-323 Ma) and release spectra which show evidence of a Late Paleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
5
13
0
Order By: Relevance
“…4B) suggest a phase of localized uplift related to this transpression. Evidence for structural thickening and associated uplift can be found in the younger hornblende ages for the northwest side of the fault (West et al, 1989), which suggests burial by oblique thrusting. Additional support for localized uplift in the Casco Bay area is provided by the pattern of current indicators in the late Paleozoic (310-280 Ma) basins to the northeast.…”
Section: Structural History Of the Casco Bay Regionmentioning
confidence: 95%
See 1 more Smart Citation
“…4B) suggest a phase of localized uplift related to this transpression. Evidence for structural thickening and associated uplift can be found in the younger hornblende ages for the northwest side of the fault (West et al, 1989), which suggests burial by oblique thrusting. Additional support for localized uplift in the Casco Bay area is provided by the pattern of current indicators in the late Paleozoic (310-280 Ma) basins to the northeast.…”
Section: Structural History Of the Casco Bay Regionmentioning
confidence: 95%
“…The Saco-Harpswell sequence southeast of the Flying Point fault shows older hornblende ages of 355-324 Ma. The younger high-temperature hornblende ages in the Falmouth-Brunswick sequence northwest of the Flying Point fault were interpreted (West et al, 1989) to reflect a late Paleozoic thermal event, but the relationship to regional deformation at that time was unclear. The rocks northwest of the Flying Point fault show evidence for strong internal shearing as a phase of oblique dextral thrusting and might be linked to this suggested thermal event.…”
Section: Thermochronology and Deformationmentioning
confidence: 99%
“…A program of 40 Ar-39 Ar dating in south-central Maine by West et al (1988), has shown that hornblende gives plateau ages of 368 to 372 Ma in the northeast, decreasing in age across 40 km toward the southwest to 323 Ma. They interpreted this pattern to reflect slow cooling in response to differential unroofing following Acadian metamorphism, in which more deeply buried rocks to the south cooled later.…”
Section: Late Pennsylvanian In New Hampshire and Mainementioning
confidence: 98%
“…The start of dextral deformation and the initiation of the regionally extensive NFS is suggested to be syn-to post-metamorphism, based on microstructural studies that indicate amphibolite facies mineral growth during dextral deformation (West and Lux, 1993;Price et al, 2010). Dextral shear along the fault system has been interpreted to have initiated in the Middle Devonian by 380 Ma based on 40 Ar/ 39 Ar hornblende data (West et al, 1988;Ludman and West, 1999) and U-(Th)-Pb zircon and monazite ages (Gerbi and West, 2007). A wider zone of dextral shear developed during the Late Devonian to Early Carboniferous (West and Hubbard, 1997).…”
Section: The Norumbega Fault Systemmentioning
confidence: 99%
“…Outcrops of the NFS in ME were examined at three primary locations (see below). Each outcrop location has been defined as the Norumbega fault system by others (West et al, 1988(West et al, , 1995(West et al, , 1999Price et al, 2010), and were examined in this study to document key characteristics of the NFS.…”
Section: The Norumbega Fault System In Mementioning
confidence: 99%